2021
DOI: 10.21462/jeltl.v6i3.663
|View full text |Cite
|
Sign up to set email alerts
|

Translation Techniques of Medical Terms Found in Covid-19 Guidebook

Abstract: <p><em>This study </em><em>was conducted </em><em>to find and analyze the use of translation techniques used by translators in translating various medical terms contained in the COVID-19 guidebook</em><em> </em><em>based on the theory from Rask (2008)</em><em>.</em> <em>The categories of medical terms used in this study are</em><em> medical terms, epidemiological terms, </em><em>and </em><em>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…It is also in harmony with the research findings of Restiana & Nugroho (2021) that Establish Equivalence as the technique with the highest frequency. Intriguingly, it may be observed that translators are particularly concerned about the original language's grammatical structures.…”
Section: Discussionsupporting
confidence: 80%
“…It is also in harmony with the research findings of Restiana & Nugroho (2021) that Establish Equivalence as the technique with the highest frequency. Intriguingly, it may be observed that translators are particularly concerned about the original language's grammatical structures.…”
Section: Discussionsupporting
confidence: 80%